Spatial Typology of the Ageing Process in the European Union on the Level NUTS 2 Regions - Ivan Šotkovský (European Regional Science Association (ERSA), 2014)
The article is deal with the spatial differences of the demographic events between European Union regions. We are research spatial diferencies of ageing process between 272 NUTS 2 regions today. The analyses on this spatial level are working with the creation of cartogram method for processing of the demographical data. We can use ArcGIS 10.2 and his version ArcMap 10.2 as a complete system for authoring, serving, and using geographic informations for better processing the spatial data by the help of cartogram method. Our principal main is to group the all 272 EU NUTS 2 regions on the basis children and elderly substitution in population and evaluation of the ageing process. Therefore we are using the basic measurement methods for examination of the age structure. The spatial typology is carried out on the basis of a series of values of the following three basic demographical indices: the children ration, the eledrely ratio, the ageing index (IA) and the dynamic ageing index (DAI). The world's current ageing index is about 30. And only in Europe is more than 100 and in European Union actually 117. This mean, that in Europe we have more elderly people than children. Only eight countries has ageing index less than 100 in European Union now. Ageing index 125 and more has six countries yet.
Keywords: C46; J11; J13; J14; R23; 330